Penerapan Metode Abc (Activity Based Costing) Dalam Menentukan Harga Jual Kamar Hotel “X” ( Studi Pada Salah Satu Hotel Berbintang Di Surabaya ) - Widiar Onny Kurniawan (Journal of Economics Development Issues, 2019)
Increasing competition in the hospitality industry, making hotels should increase the advantage in competing. An important part of improving the competitive advantage of hotels is to set, measure and allocate accurately the costs to be efficient. Cost efficient will help managers to make decisions so as to increase the occupancy rate of hotels that ultimately impact on profit. Researchers conducted research on the Hotel "X" located in the city of Surabaya where this hotel is one of the oldest four-star hotel in the city of Surabaya. Determination of the cost as the cost of room rental at Hotel "X" is still using the traditional method of the cost of renting each room on the same "X" Hotel. The purpose of this study is to know the application of Activity Based Costing (ABC) method in the calculation of service fee and the determination of the hotel room rental price "X". The technique of data analysis performed is to analyze the traditional method that is being used by Hotel "X" and compare with ABC method. The results of this study is the calculation of the cost of room rental using ABC method is more accurate when compared with traditional methods. Hotel "X" should consider undercost in the cost of room rental so that the hotel does not suffer long-term losses resulting in earnings.